Comprehensive Hematological and molecular Characterization of hemoglobin Hekinan [α27(B8)Glu→Asp(α1), HBA1:c.84G > T] in a Large Thai cohort - Amornchai Suksusut; Jidapa Jaitheang; Manussavee Prapphal; Pranee Sutcharitchan; Ponlapat Rojnuckarin; Noppacharn Uaprasert (Hematology)
Background: Hemoglobin (Hb) Hekinan is a prevalent α-globin variant frequently missed in thalassemia screening centers using high-performance liquid chromatography (HPLC) or capillary electrophoresis. This study aims to investigate the hematological and molecular characteristics of Hb Hekinan in a large cohort.Methods: Hb variants were identified using isoelectric focusing (IEF) and HPLC. Hb Hekinan was confirmed by direct DNA sequencing. Additional genetic determinants, including α-thalassemia, β-thalassemia and other variants, were detected using multiplex GAP-PCR, ARMS-PCR or direct DNA sequencing as appropriate.Results: Among 61,997 Hb typing samples, 149 cases of Hb Hekinan were identified in Thai individuals and classified into 8 genotypic groups. These included 104 Hb Hekinan heterozygotes, 10 Hb Hekinan coexisting with α+-thalassemia, 3 Hb Hekinan with non-deletional α-variants, 6 Hb Hekinan with α0-thalassemia, 21 double heterozygote for Hb Hekinan and HbE, 3 Hb Hekinan with β-thalassemia trait, 1 triple heterozygotes (Hb Hekinan/α0-thalassemia/Hb E) and 1 quadruple heterozygote for Hb Hekinan/α+-thalassemia/Hb E/Hb Hope. Hb Hekinan was well-separated from Hb A using IEF but was frequently missed with HPLC. On HPLC, Hb Hekinan could only be identified when coexisting with α0-thalassemia. All cases presented with either normal Hb levels or mild anemia.Conclusions: Hb Hekinan is a prevalent α-globin variant that is often undetected by HPLC but reliably identified using IEF. These findings highlight the importance of incorporating IEF for accurate diagnosis of Hb Hekinan. Most cases are clinically benign, even when interacting with other thalassemia syndromes or Hb variants.